Evaluation of risk factors for catheter-related infections with gram-negative bacteria in Tehran, Iran - Tahereh Malakoutian; Mehdi Zahmatkesh; Ali Kabir (Journal of Nephropharmacology, 2022)
Introduction: Catheter infection is due to gram-negative, gram-positive bacteria, and fungi. Gram-positive bacteria are the most prevalent cause of catheter infection, although gram-negative bacteria seem to have escalated in recent years, which may have numerous risk factors. In this report, we intended to study these risk factors. Objectives: This study aimed to investigate the risk factors for catheter-related infections caused by gram-negative bacteria in hemodialysis patients, to prevent catheter-related infections, which are unfortunately abundant. Patients and Methods: This cross-sectional study was conducted on128 hemodialysis patients known cases Hasheminejad hospital in Tehran, Iran in 2019. Patients were assigned into two groups as the case group (catheter-related infection caused by gram-negative bacteria) (n=64) and the control group (catheter-related infection caused by gram-positive bacteria) (n=64). Risk factors for catheter-related infection, including hemoglobin, phosphorus, albumin, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), total iron-binding capacity (TIBC), catheter insertion site, urinary tract infection (UTI), urinary tract manipulation, and urinary tract anomalies were obtained and analyzed via SPSS version 26. Results: Two groups were significantly different in serum albumin level (3.7±0.5 g/dL in gram-negative group and 3.9 ± 0.5 g/dL in gram-positive group; P=0.009) and in UTI (23.4 % in gram-negative group and 7.8 % in gram-positive group; P=0.015). Additionally, no significant differences were observed in serum ferritin, phosphorus, ESR, CRP, TIBC, duration, and site of catheter insertion. Regression analysis shows that, for every unit increase in albumin, the chance of developing a gram-negative catheter infection is 0.356, or about one-third. In other words, with decreasing each unit of albumin, the chance of a gram-negative catheter infection is 2.8 times (reverse 0.356). Conclusion: Serum albumin levels were significantly low in gram-negative group. Moreover, UTIs were significantly higher in this group. It is also important to consider hypoalbuminemia and UTI as risk factors for catheter infection with gram-negative bacteria.